ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI RETURN SAHAM: Kasus pada Perusahaan Manufaktur yang Go Public di BEI periode tahun 2005 - 2009 - Arista, Desy; Astohar, Astohar (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2012)
Problems in the study of some previous studies showed inconsistent results, thisresearch was conducted to re-examine the influence of fundamental factors consistingof return on assets (ROA), debt to equity ratio (DER), earnings per share (EPS), andprice to book value (PBV) together and partial effect on Stock Return manufacturingcompanies in Indonesia Stock Exchange in 2005-2009.The sample size used in this study was of 114 manufacturing companies went public onthe Stock Exchange with the determination of the sample using purposive sampling. Thetype of data using secondary data using documentation.Return on assets (ROA) has no significant effect on stock return manufacturingcompanies listed on the Indonesia Stock Exchange. Debt to equity ratio (DER) has asignificant influence on stock return manufacturing companies listed on the IndonesiaStock Exchange. Earning per Share (EPS) has no significant effect on stock returnmanufacturing companies listed on the Indonesia Stock Exchange. Price to book value(PBV) has a significant influence on stock return manufacturing companies listed onthe Indonesia Stock Exchange. Taken together (simultaneously) return on assets, debtto equity ratio, earnings per share and price to book value has a significant influenceon stock return manufacturing companies listed on the Indonesia Stock Exchange.Keywords: Return on Assets, Debt To Equity Ratio, Earning Per Share, Price To BookValue and Stock Return